(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The Manas epic is a unique phenomenon of world culture, reflecting the centuries-old history and life of the Kyrgyz people. This article attempts to deeply analyse the ethnic motifs present in this grandiose work. The scientific article focuses on identifying and interpreting the ethnic features underlying the epic. The images of different ethnic groups, their relationships, cultural features and historical fates as they are presented in the epic text are analysed. Special attention is paid to the historical context in which these images were formed and transformed. The research article has systematised ethnic motifs, analysed historical prototypes, studied ethnic stereotypes and determined the function of ethnic motifs. The novelty of the scientific article lies in the application of an interdisciplinary approach combining historical, folkloristic and linguistic methods, which allows to get a more complete picture of the interaction of ethnic groups in the region. The following methods were used in the research: comparative-historical analysis, structural analysis of the text, component analysis, as well as the method of comparison with other epic works of Turkic peoples. Special attention was paid to the historical prototypes of ethnic groups reflected in the epic images, as well as the role of ethnic motifs in the formation of the national identity of the Kyrgyz. Key words: Manas epic, ethnic motifs, historical context, mythology, Central Asia, Kyrgyz, ethnogenesis, ethno-cultural interaction, folklore, hermeneutics.